TRENDS IN THE DEVELOPMENT OF HIGHER MEDICAL EDUCATION THROUGH THE INTRODUCTION OF DIGITAL ONLINE CONSULTATIONS IN SURGERY - Ulugbek K. Kasimov; Fayzrakhmon M. Abdurakhmanov; Azam R. Bobobekov; Diyora U. Sultanova (Central Asian Journal of Medicine, 2022)
The digitalization of medicine has been actively introduced into medicine in recent decades. Telemedicine is a variation of this area. It has prospects in the form of conducting various online consultations of specialists in all corners of our Republic, when the use of electronic information, integrated digital and telecommunication technologies creates conditions for the exchange of data between doctors, as well as for management in the field of medical education and healthcare. With the help of telemedicine technology, doctors can urgently consult with each other. In serious cases, doctors themselves sometimes need the help of a more qualified specialist. If there is no such thing nearby (for example, if we are talking about remote medical institutions), then the only way out is a video call to an experienced colleague. Doctors can also send patient data to each other to view their medical history. Live broadcasts of surgical operations, during which doctors and students can ask their questions, which will qualitatively improve the educational process.